Isolation: The experience of adolescent motherhood in Laos - Thongmixay, Souksamone; Essink, Dirk; Kahrs, Taewee; Vongxay, Viengnakhone; Wright, Pamela; Sychareun, Vanphanom; Broerse, Jacqueline E. W. (Frontiers in Global Women's Health, 2023)
Background Teenage pregnancy is a persistent public health problem with pervasive socio-economic consequences, particularly in in low- and middle-income countries, often related to low social participation and low economic security. The experiences of adolescent pregnancy and motherhood have seldom been described from a personal point of view. This study aimed to gain insights into how adolescent mothers in Laos experience their motherhood, how they perceive their situation and try to cope with it. Methods This qualitative study was undertaken with 20 pregnant adolescents and young mothers living in peri-urban areas in two of the 18 provinces in Laos. Data were collected during 20 semi-structured interviews and two focus group discussions (n = 10). Digital recordings were transcribed verbatim, summarised and thematically analysed using an inductive analysis and exploratory approach. Results The most common theme was that the young mothers experienced exclusion individually, socially and in relation to official systems. In only two cases was the pregnancy intended. All were determined to be good mothers, but were overwhelmed and unsure how to overcome structural barriers to educational, social and economic participation. Conclusion Participants revealed that their adolescent pregnancy was tied to losses of past and future aspirations, and believed that working to prevent unintended adolescent pregnancy is worthwhile, but also advised that community support structures would help young women in their position.